Fiestas of the Philippines - Gibb, Hugh. ([Manila] Felta Book Sales, 1981)
Focuses on some spectacular Philippine festivals which pertain to farming, penance and the passion of Christ.
VHS.
Keywords: Festivals -- Philippines